Dynamics of luffing motion of a flexible knuckle boom crane actuated by hydraulic cylinders. (January 2020) - Cibicik, Andrej; Pedersen, Eilif; Egeland, Olav
Highlights: A general dynamic modeling procedure for planar flexible manipulators. A general procedure for force analysis of planar flexible manipulators. Rigid body velocities and velocities caused by elasticity are represented as twists. Coupling of dynamics of a manipulator and hydraulic cylinders using bond graph. An implementation example for a planar flexible knuckle boom crane. Abstract: In this paper we present a modeling procedure for a flexible knuckle boom crane, which is actuated by hydraulic cylinders and is modeled as a planar multibody system. We propose a convenient framework where both rigid body velocities and velocities caused by flexible behavior are represented as twists. Such formulation allows for using screw transformations, which leads to systematic derivations. Dynamics of a crane and mass balance of hydraulic cylinders are coupled using the bond graph method. In addition, we present a procedure for the determination of reaction forces in passive joints, which is conveniently given as an extension of the dynamic modeling procedure. Both procedures are presented in a general and systematic manner such that they can be applied for a group of planar flexible manipulators. We study the dynamics of luffing motion of a crane by numerical simulation and provide the simulation results, as well as determine the reaction forces in passive joints. The simulation results are validated by the ANSYS finite element analysis. The derived model provides a basis for design of luffing cylinders and can potentially be used for studying performance of a crane control system.